Examining the Impact of Molten Plastic Variation on the Strength of Interlocking Bricks Using Response Surface Methodology - Carter, Daniel; Singh , Priya (Ayden Journal of Engineering and Applied Sciences, 2024)
This studied investigate the variation of molten plastic on the strength of plastic interlocking brick using response surface method and ANSYS FEM software. plastics, being one of the most commonly generated waste in today's culture and also one of the most easily recyclable materials that may be able to replace traditional clay and sand bricks Plastics interlocking brick s tests include compressive strength tests, in which the brick specimen is placed in a bricks testing machine that gradually increases the load until the specimen's resistance to the growing pressure breaks down and it can no longer tolerate any further strain. This increased from 10.5N/mm2 to 14.0N/mm2 by volume after 7days with a control specimen of M1. The maximum increase in flexural strength test for M5 and M6 was in order of 6.4N/mm2 and 7.1N/mm 2 respectively.